Budgetary Impacts of Adding Agricultural Risk Management Programmes to the CAP. (7th October 2020) - Pieralli, Simone; Pérez Domínguez, Ignacio; Elleby, Christian; Chatzopoulos, Thomas
Abstract: Volatile prices and income uncertainties are major issues for farmers, leading to a demand for policies that mitigate such risks. However, the budgetary consequences of risk management schemes are uncertain due to their dependence on market prices. Using an agricultural multi‐commodity market model, we evaluate the potential budgetary consequences of introducing two specific risk management schemes used in the United States into the European Union Common Agricultural Policy (CAP), namely the Agriculture Risk Coverage (ARC) and Price Loss Coverage (PLC) programmes. Our analysis considers three sets of reference prices and stochastic uncertainty related to yields and macroeconomic conditions, resulting in a joint distribution of agricultural outputs and support payments. The results show that the payments from these two risk management schemes are sensitive to the reference prices triggering support and to the programme participation shares. In the most extreme stochastic simulations, support payments from the PLC programme reach €23 billion while support payments from the ARC programme reach €2.1 billion for the three crops considered (barley, wheat and maize).